Study on enhancing of the surge current capabilities of embedded SBDs in SWITCH-MOSs and body-PiN-diodes in SiC trench MOSFETs. (1st April 2023) - Kitamura, Yudai; Kato, Fumiki; Tanaka, So; Tawara, Takeshi; Harada, Shinsuke; Sato, Hiroshi; Yano, Hiroshi; Iwamuro, Noriyuki
Abstract: This study investigates the surge current capabilities of embedded Schottky barrier diodes (SBDs) in SiC SBD-integrated trench metal–oxide–semiconductor field effect transistors (MOSFETs) (SWITCH-MOSs) using titanium and nickel for the Schottky metals. The results demonstrated that a 25% enhanced surge current capability can be achieved for an embedded SBD with a higher barrier height of nickel compared to those with titanium and that it was comparable to body-PiN-diodes in a standard SiC trench MOSFET (IE-UMOSFETs). Furthermore, the study demonstrated the superior surge current capabilities of body-PiN-diodes in IE-UMOSFETs that have wide and thick Cu heat capacitance blocks attached to chip surfaces, and a significant improvement of 57% in surge current capability was achieved with 2.9 × 4.1 mm 2 wide and 0.4 mm thick Cu blocks. Notably, there was no sacrifice of I – V characteristics in the third quadrant and reverse recovery characteristics or the resistance in the first quadrant with the Cu blocks.